Analysis of the Selection of General Contract Conditions for Toll Projects in South Sumatra Province - Adi, Mochamad Waskito; Wiguna, I Putu Artama (Riviera Publishing, 2026)
Toll road projects utilizing turnkey contract schemes, initially slated for completion between 2016 and 2019, experienced significant delays due to land unavailability and funding constraints. By 2019, construction progress on the Kayu Agung–Palembang–Betung (KAPALBETUNG) project had reached only 51%. To achieve functional targets, the project owner implemented a strategic policy to complete work up to Station 41+000 and construct a temporary toll exit, requiring an additional budget of approximately IDR 50 billion. The subsequent phase continued from late 2021 to 2023 under a single contract with the first phase but faced further complications from additional land acquisition, cost escalation, and schedule deviations. These conditions heightened the risk of construction disputes. This research aims to identify and formulate criteria and sub-criteria for dispute resolution using the Modified Delphi method and to determine the optimal contract alternative through the Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE). Data were collected via literature review and in-depth interviews and validated through five rounds of Modified Delphi. Results indicate the priority weights of criteria as Schedule (35.00%), Cost (32.22%), and Quality (32.78%). PROMETHEE analysis reveals that the NEC4 Engineering and Construction Contract (ECC) is the most optimal alternative for mitigating potential disputes. This study contributes to strategic decision-making in managing dispute risks within complex, dynamic construction projects.